Application of Antiviral, Antioxidant and Antibacterial Glycyrrhiza glabra L., Trifolium pratense L. Extracts and Myristica fragrans Houtt. Essential Oil in Microcapsules - Jurga Andreja Kazlauskaite; Inga Matulyte; Mindaugas Marksa; Raimundas Lelesius; Alvydas Pavilonis; Jurga Bernatoniene (MDPI AG, 2023)
Viruses and bacteria can disrupt normal human functions; therefore, ways to use the beneficial properties of plants to promote health are constantly being researched. Plant materials that accumulate biologically active compounds can be used to create a new pharmaceutical form. This study aimed to investigate the biological activity of selected plant extracts and essential oil and to produce microcapsules. The main compounds in extracts and essential oil were determined using chromatographic methods, antioxidant activity was evaluated spectrophotometrically, antimicrobial activity was assessed by monitoring the growth of nine pathogens, and the antiviral effect on infected bird cells with coronavirus was evaluated. Trifolium pratense L. extract had the highest antioxidant (26.27 ± 0.31 and 638.55 ± 9.14 µg TE/g dw by the DPPH and ABTS methods, respectively) and antiviral activity (56 times decreased titre of virus). Liquorice extract expressed antibacterial activity against Gram-positive pathogens and the highest antioxidant activity using the FRAP method (675.71 ± 4.61 mg FS/g dw). Emulsion stability depended on excipients and their amount. Microcapsules with extracts and essential oil were 1.87 mm in diameter, and their diameter after swelling was increased more than two times in intestinal media, while less than 0.5 times in gastric media.